NILAI MORAL DALAM CERITA RAKYAT DAERAH DANAU KERINCI - Salsabilla, Junifa; Wibowo, R. Imam Suwardi; Akhyaruddin, Akhyaruddin (Universitas Negeri Makassar, 2024)
This study aims to describe the moral values in the folklore of the Kerinci Lake region. This research includes qualitative research with research data that is quantitative data and uses literature study techniques to collect data. The source of data in this research is the story of Baskom Emas, Puti Sari Jelio, Putri Tangguk, Sari Bangkuk published in the book Folklore of Lake Kerinci. The research data was analysed with the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that the moral value in the folklore of Lake Kerinci contains the moral value of lazy attitude, attitude towards parents, hardworking attitude, despicable attitude, obedient to parental advice, disobedient to parents and God's reply to the character.